2009
DOI: 10.1109/jmems.2009.2025999
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Parametric Sensitivity in Electrically Coupled MEMS Resonators

Abstract: We use vibration localization as a sensitive means of detecting small perturbations in stiffness in a pair of weakly coupled micromechanical resonators. For the first time, the variation in the eigenstates is studied by electrostatically coupling nearly identical resonators to allow for stronger localization of vibrational energy due to perturbations in stiffness. Eigenstate variations that are orders of magnitude greater than corresponding shifts in resonant frequency for an induced stiffness perturbation are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
107
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 20 publications
5
107
0
Order By: Relevance
“…It was demon-20 strated that by measuring the eigenstates shift caused by mode localization, orders of magnitude improvement in sensitivity of mass change was observed [10]. Various groups demonstrated that orders of magnitude enhancement in sensitivity of stiffness change [12,13,14,15] and force [16] could be achieved using this approach. Another advantage of this type of device is its intrinsic 25 common mode rejection [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was demon-20 strated that by measuring the eigenstates shift caused by mode localization, orders of magnitude improvement in sensitivity of mass change was observed [10]. Various groups demonstrated that orders of magnitude enhancement in sensitivity of stiffness change [12,13,14,15] and force [16] could be achieved using this approach. Another advantage of this type of device is its intrinsic 25 common mode rejection [17].…”
mentioning
confidence: 99%
“…Assume a quality factor of Q = 2 × 10 4 in vacuum, which is a conservative 245 estimation compared to other similar devices [12,33] and setting |K/K c | = 200, …”
mentioning
confidence: 99%
“…[9][10][11][12][13][14] When the resonators are identical, the vibration of the eigenmodes is delocalized over the array. In a similar way to the Anderson's localization, the addition of the mass on one of the resonators leads to the spatial localization of the eigenmodes.…”
mentioning
confidence: 99%
“…The extent of this vibration energy confinement depends not only on the magnitude of the induced disorder, but also on the strength of internal coupling between the resonators with weaker coupling resulting in stronger localization of the vibration modes [7]. It is also known that weakly coupled, nearly identical resonators exhibit an abrupt divergence of the loci of their eigenvalues when these are plotted against a parameter representing the symmetry-breaking disorder in the system [8,9].…”
Section: Mode Localization and Curve Veeringmentioning
confidence: 99%
“…2. The relative shifts in the magnitudes of the normalized eigenvectors (eigenstates) due to small perturbations in stiffness of one of the resonators may then be expressed as [7] ). 2 , 1 ( ;…”
Section: Mode Localization and Curve Veeringmentioning
confidence: 99%